Avaliação clínico-laboratorial de gatos domésticos obesos e em sobrepeso - Karina Roque Silva (2019)
The prevalence of obesity and its association with metabolic diseases has been a growing concern in veterinary medicine. The cats, like humans, present a set of metabolic abnormalities such as insulin resistance and type 2 diabetes mellitus. In humans the set of changes in energy metabolism associated with risk factors for diseases is known as metabolic syndrome. For obese cats it is necessary to establish objective biochemical and mechanical parameter even as their reference values for better characterization of the syndromed. The objective of this work was to characterize the metabolic profile and feeding management of a population of obese and overweight cats. It was evaluated 84 cats that were classified according to body condition index and percentage of body fat into obese, lean and overweight. To the clinical biochemitry parameters were included serum lipids: triglycerides (TG), cholesterol, lipoproteins (HDL, LDL and VLDL), non-esterified fatty acids (NEFA) and betahydroxybutyrate (BHB). Data were submitted to multivariate statistical analysis. The biochemical parameters that differentiate from the obese animals of the lean cats were triglycerides and ALT. The overweight animals were not differentiated from the obese through these analytes. This study detected that serum ALT and TG can characterize the metabolic syndrome in obese felines and can be used as predictive tools in the classification of the obese animal with this disorder.